Bovine Papillomavirus Type 13 Expression in the Urothelial Bladder Tumours of Cattle. Issue 6 (19th January 2015) - Roperto, S.; Russo, V.; Leonardi, L.; Martano, M.; Corrado, F.; Riccardi, M. G.; Roperto, F.
Summary: Bovine papillomavirus type 13 (BPV‐13), a novel Deltapapillomavirus, has been found associated with urothelial tumours of the urinary bladder of cattle grazing on lands infested with bracken fern. BPV‐13 was detected in 28 of 39 urothelial tumours. Diagnosis was based on sequencing of L1 and E5 amplicons from tumour samples. The nucleotide sequences generated from these amplicons showed a 100% homology with the sequences of BPV‐13 L1 and E5 DNA found in Brazil from a fibropapilloma of the ear in a cow and from equine sarcoids in two horses. GenBank accession number of our representative BPV‐13 sequences isJQ798171.1 . Furthermore, mRNA encoding BPV‐13 E5 oncoprotein was also documented, and its expression was also shown by immunohistochemistry and immunofluorescence in the basal and suprabasal urothelial tumour cells. In twenty‐three tumours, BPV‐13 was simultaneously found with BPV‐2, a Deltapapillomavirus genus, species 4. The latter virus was detected by amplifying and sequencing a 154‐bp‐sized DNA fragment of BPV‐2 E5. In addition, BPV‐13 by itself was seen to be expressed in five BPV‐2‐negative urothelial tumours. This study shows that BPV‐13 is present in urothelial tumour cells thus sharing biological properties with BPV‐1 and BPV‐2. Although further studies are needed, BPV‐13 appears to be another worldwide infectious agent responsible for a distressing disease causing severe economic losses in cattle industry.